An upper bound for the distance to finitely generated ideals in Douglas algebras - Gorkin, Pamela (2001)
Let f be a function in the Douglas algebra A and let I be a finitely generated ideal in A. We give an estimate for the distance from f to I that allows us to generalize a result obtained by Bourgain for H∞ to arbitrary Douglas algebras.